Electromechanical behaviors of a PVDF beam-film coupled energy harvester under droplet impact - Weijia Yang; Guannan Hao; Zhinan Li; Shuai Zhang; Lixin Lu (PLoS ONE, 2025)
Droplet-based harvesters can effectively transfer the kinetic energy of impacting water droplet into electrical energy. Based on conventional cantilever structure of harvesters, a beam-film coupled structure is developed by extending the piezoelectric film along the beam length to enhance the power generation. First, the droplet impact force is modeled based on impulsive theorem, which is applied in constructing the simulation model of the proposed harvester using COMSOL. Second, the developed model is validated by comparing with experimental results. Then the dynamic response and electromechanical coupling effect of the proposed structure under droplet impact are comprehensively analyzed. Results show that the energy density of beam-film coupled structure with film ratios 0.6 and 0.8 is much higher than that of cantilever structure, showing an increase of 522.67% and 645.18% respectively. Moreover, the harvester with film ratio 0.6 always generates greater total electrical energy collected than the film ratio 0.8, and the difference between them becomes more significant for higher impact velocities> 1.25m/s and larger droplet diameters > 3.2mm. Results also show that there exist optimal structural parameters of the harvester which lays a foundation for further structural optimization to continuously improve the energy conversion efficiency.